An Evaluation of Persuasive Systems on Private Music School Websites Using the Persuasive System Design Model - Hasugian, Leonardi Paris; Zeko, Chubo; Ahmadimaldeh, Ashkan; Carolina, Anita; Muqtadiroh, Feby Artwodini; Rakhmawati, Nur Aini (Society of Visual Informatics, 2025)
Music is one of the business opportunities within the creative industry, and the number of music schools is rapidly increasing in major urban areas. The City of Oulu in Finland has various music school providers that use websites as digital portals of information about their schools. Given the critical role of persuasive websites in marketing, this study aims to evaluate the websites of private music school providers in Oulu, with a persuasive system approach. To achieve this objective, a content analysis was conducted on fifteen websites and studied how they influence their users persuasively. Our method analyzes the website using a checklist-based approach grounded in the Persuasive System Design model, which comprises 28 principles categorized into four groups, namely: Primary Task Support, Dialogue Support, System Credibility Support, and Social Support. The analysis revealed that implementation of persuasive principles was uneven across the website, with the following average application rates per category: 28.57% (Primary Task Support), 28.57% (Dialogue Support), 38.10% (System Credibility Support), and 9.52% (Social Support). Several providers have applied the Persuasive System Design model according to each category, but not optimally. These findings suggest that there is still considerable room for improvement in the websites of private music schools through an optimally persuasive approach to support and motivate users to access information. The implication can encourage providers to optimize their website persuasively, engaging a broader audience and serving users properly.